Global, regional, and country level need for data on wastewater generation, treatment, and use - Sato, T.; Qadir, Manzoor; Yamamoto, S.; Endo, T.; Zahoor, A. (Elsevier, 2013)
Irrigation with wastewater supports agricultural production and the livelihoods of millions of smallholder farmers in many parts of the world. Considering the importance of better wastewater management at the local and national levels, there is a need for updated national data on wastewater generation, treatment, and use, which would also assist in regional and global wastewater assessments. While searching data and literature in published or electronic forms for 181 countries, we find that only 55 countries have data available on all three aspects of wastewater - generation, treatment, and use. The number of countries with one or two aspects of wastewater generation, treatment, and use is 69, while there is no information available from 57 countries. Of the available information, only 37% of the data could be categorized as recent (reported during 2008-2012). The available data suggest that high-income countries on average treat 70% of the generated wastewater, followed by upper-middle-income countries (38%), lower-middle-income countries (28%), and low-income countries, where only 8% of the wastewater generated is treated. The availability of current information on wastewater generation, treatment, and use is crucially important for policy makers, researchers, and practitioners, as well as public institutions, to develop national and local action plans aiming at safe and productive use of wastewater in agriculture, aquaculture, and agroforestry systems. The country level information aggregated at the regional and global levels would help in identifying the gaps in pertinent data availability and assessing the potential of wastewater in food, feed, and fish production at different scales.